50 years of Arabidopsis research: highlights and future directions. Issue 3 (14th October 2015) - Provart, Nicholas J.; Alonso, Jose; Assmann, Sarah M.; Bergmann, Dominique; Brady, Siobhan M.; Brkljacic, Jelena; Browse, John; Chapple, Clint; Colot, Vincent; Cutler, Sean; Dangl, Jeff; Ehrhardt, David; et al.
Summary: The year 2014 marked the 25 th International Conference on Arabidopsis Research. In the 50 yr since the first International Conference on Arabidopsis Research, held in 1965 in Göttingen, Germany, > 54 000 papers that mention Arabidopsis thaliana in the title, abstract or keywords have been published. We present herein a citational network analysis of these papers, and touch on some of the important discoveries in plant biology that have been made in this powerful model system, and highlight how these discoveries have then had an impact in crop species. We also look to the future, highlighting some outstanding questions that can be readily addressed in Arabidopsis. Topics that are discussed include Arabidopsis reverse genetic resources, stock centers, databases and online tools, cell biology, development, hormones, plant immunity, signaling in response to abiotic stress, transporters, biosynthesis of cells walls and macromolecules such as starch and lipids, epigenetics and epigenomics, genome‐wide association studies and natural variation, gene regulatory networks, modeling and systems biology, and synthetic biology. Contents Summary 922 I. Introduction and a brief survey of 54 033 Arabidopsis publications 922 II. Arabidopsis reverse genetics: paving the way for gene function studies 922 III. Arabidopsis stock centers 925 IV. Databases and online tools 925 V. Cell biology 926 VI. Development 927 VII. Hormones 928 VIII. The plant immune system and Arabidopsis research 929 IX. Signaling in response to abiotic stress 930 X. Pumps, channels, transporters and the like 931 XI. Cell walls, starch and lipids 932 XII. Epigenetics and epigenomics: from genotype to phenotype 933 XIII. Natural variation and genome‐wide association studies 934 XIV. Gene regulatory networks 934 XV. Modeling, bioinformatics, systems biology 935 XVI. Synthetic biology 936 XVII. Conclusions and outlook 937 Acknowledgements 937 References 937